Osteoprotegerin is a new independent predictor of the progression of cardiovascular pathology: chronic heart failure associated with type 2 diabetes and osteoporosis - A. T. Teplyakov; E. N. Berezikova; S. N. Shilov; A. A. Popova; I. V. Yakovleva; A. V. Molokov; E. V. Grakova; K. V. Kopeva; A. V. Svarovskaya; O. V. Garmaeva; Yu. Yu. Torim; E. I. Stepachev; et al. (Бюллетень сибирской медицины)
Aim. To study the link of increased serum concentrations of osteoprotegerin (OPG) in patients with chronic heart failure (CHF) associated with type 2 diabetes mellitus (DM 2), osteoporosis or osteopenia with the development of cardiovascular events (primarily, decompensation of CHF, including those requiring hospitalization, death from cardiovascular disease, acute coronary syndrome or acute ischemic stroke) to determine the possibility of using this biomarker as a predictor of a severe course of cardiovascular disease in these patients.Materials and methods. In a 12-month cohort observational study included 75 patients (mean age 57.4 ± 5.4 years) with CHF associated with DM 2, osteoporosis or osteopenia. Cardiovascular events were analyzed in three groups of patients formed based terteling ranges of concentration of the OPG level in serum: in the 1st group (n = 25) included patients with serum OPG concentration is less than 5.0 pmol/l; in the 2nd group (n = 25) OPG level of 5.0–7.2 pmol/l; in the 3rd group (n = 25) - with the content of OPG more than 7.2 pmol/L. The serum OPG, tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) serum levels were determined by ELISA. Assessment of bone mineral density (BMD) was performed by a densitometric method using dual-energy X-ray absorptiometry.Results. Highly reliable increased expression of OPG in 2 and 3th tertiles was found in patients with CHF associated with type 2 diabetes in comparison with the control group. The frequency of adverse events gradually increased from the 1st tertile to the 3rd tertile OPG. With the median for OPG more than 5.2 pmol/L and BMD less than -2.5 standard deviations, the highest frequency (60.9%) of adverse cardiovascular events was identified. A close correlation of OPG with the values of pro-inflammatory cytokines-TNF-α (r = 0.46; p = 0.019) and IL-1β (r = 0.4; p = 0.01), glycated hemoglobin (r = 0.55; p = 0.009) and the severity of CHF (r = 0.49; p = 0.013).Conclusions. Osteoprotegerin is an independent risk factor for the development of comorbid cardiovascular pathology: CHF associated with DM 2 and osteoporosis. It seems clinically justified to use OPG to stratify the risk of progression of cardiovascular pathology.